POLA REKRUTMEN CALON ANGGOTA LEGISLATIF OLEH PARTAI GERAKAN INDONESIA RAYA (GERINDRA) KOTA PEKANBARU TAHUN 2014 - Salsabila, Rhanty Syefira; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Gerakan Indonesia Raya (GERINDRA) is a relatively new political party that eligible to propose candidates for legislative council. Gerindra has it own pattern to recruit candidates that will be nominated in the 2014 second legislative elections. Gerindra implements a tight mechanism of recruitment, so that hopefully the person who will be the people’s representative is the best one, especially in Pekanbaru city council. It has been proven that in 2014 election, gerindra increased vote significantly from 2009.Starting from that background, this research aims to identify the pattern of gerindra’s recruitment since it was succeeding to raise the number of vote significantly. The method used in this study is a qualitative research method. Data collection was done by in-depth interviews to several representative informants and also documentation, data were analyzed based on the results of interviews.Recruitment pattern of gerindra begin with screening and some specific criteria were given to be fulfilled by the candidate. One of the factors that obstruct is the tight screening process so it become a hard decision to discuss because it is not easy to find a name that really fit the party’s criteria.Keywords : Recruitment pattern, political party, legislative councilcandidate